2019
DOI: 10.3389/fimmu.2019.02361
|View full text |Cite
|
Sign up to set email alerts
|

GMP-Compliant Manufacturing of NKG2D CAR Memory T Cells Using CliniMACS Prodigy

Abstract: Natural killer group 2D (NKG2D) is a natural killer (NK) cell-activating receptor that recognizes different stress-induced ligands that are overexpressed in a variety of childhood and adult tumors. NKG2D chimeric antigen receptor (CAR) T cells have shown potent anticancer effects against different cancer types. A second-generation NKG2D CAR was generated by fusing full-length human NKG2D to 4-1BB costimulatory molecule and CD3ζ signaling domain. Patient-derived CAR T cells show limitations including inability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…In previous studies, this population of CD45RA – memory T cells showed no alloreactivity when compared with the CD45RA + counterpart ( Fernández et al, 2017 ). These cells were mainly CD4+ ( Fernández et al, 2019 ) and showed effectiveness against viral infections ( Triplett et al, 2015 ). Phenotypically, we found that CD45RA – memory T cells were fully capable of producing IFN-γ in the presence of SARS-CoV-2-specific peptides.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, this population of CD45RA – memory T cells showed no alloreactivity when compared with the CD45RA + counterpart ( Fernández et al, 2017 ). These cells were mainly CD4+ ( Fernández et al, 2019 ) and showed effectiveness against viral infections ( Triplett et al, 2015 ). Phenotypically, we found that CD45RA – memory T cells were fully capable of producing IFN-γ in the presence of SARS-CoV-2-specific peptides.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them still need to be coupled to different devices for the sequential steps of the production process [72][73][74][75][76]. A fully automated closed system, the CliniMACS prodigy (Miltenyi Biotec, Germany), has been recently proposed and validated for lentiviral transduced CAR T-cells in several clinical experimental settings [77][78][79].…”
Section: Qualitymentioning
confidence: 99%
“…Use of CAR T cells created using spacers with suboptimal length results in off-target effects. The downstream CAR component(s) are co-stimulatory domain(s) that can be shared between CAR NK and CAR T cells [ 42 , 43 ], followed by CD3ζ. With the rapid development of DNA synthesis technology, many CAR sequences are now synthesized by a vendor if the DNA sequences encoding the scFv are known.…”
Section: Introductionmentioning
confidence: 99%